(3GdCfJUGQs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdbOQI hGdLdGd hGdYR hGdSdWGf s
(3BNQgG (B:s
(3jfJgi Hhbag cGJH hCNQ GdehLhO efg bhdg (B: (3gPG eY eG ai cdGeg ef GdEbOGe Ydi gPg GdBjI GdYXjeI hEfcGQg gPg GdMLI dQShd Gddg Udi Gddg Ydjg hSde s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(2845(3c(B) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs